Various Approaches to Successful E-learning Implementations - Baloglu, Arzu (Proceedings of the International Conference on Networked Learning, 2002)
The main objective of this paper is to present a critical review concerning some advice concerning e-learning implementation. Training or web based learning will become one of the most important sectors in future. The purpose of this study is to suggest workable guideline to adapt e-learning to the practical needs and conditions of the business sector. A Global economy needs the capacity to constantly update the education and essential skills of its work force. That is why web based training projects are being supported by government, lecturers and the private sector. However, when e-learning programs have been successfully implemented, they have known increased productivity and than they saw that it met the expectation of management. When the implementation is unsuccessful, investment on various components such as time, resource and capital can be wasted. That is why there are some critical factors which need to be taken into account. We are learning from the experience of those who have applied various methods in their workplace. In this paper, together with a working definition of e-learning and its importance as well as factors critical for success various approaches to its satisfactory implementation have been included. Later on we use conclusion with a critical requirement and a number of individual suggestion for improvement. Finally, we document improvements, which have resulted from the application of several different approaches to training in e-learning.